Virtual Monochromatic Imaging in Patients with Intermediate to High Likelihood of Coronary Artery Disease: Impact of Coronary Calcification - Carrascosa, Patricia (2016)
Rationale and Objectives We sought to explore the image quality and diagnostic performance of virtual monochromatic imaging derived from dual-energy computed tomography coronary angiography (DE-CTCA) in patients with intermediate to high likelihood of coronary artery disease (CAD) and the influence of calcification. Materials and Methods Consecutive symptomatic patients with suspected CAD referred for invasive coronary angiography who underwent DE-CTCA and a coronary artery calcium scoring before the invasive procedure comprised the study population. Results Sixty-seven patients were included. Image quality was significantly lower at 45 keV reconstructions (mean Likert score 45 keV 3.57 ± 0.6, 65 keV 4.07 ± 0.5, and 85 keV 4.09 ± 0.6; P < .0001). Patients with moderate calcification showed a trend toward a significant improvement in the diagnostic performance with 65 keV vs 45 keV reconstructions (45 keV, area under the curve 0.92 [95% confidence interval 0.89–0.95] vs 65 keV, area under the curve 0.96 [95% confidence interval 0.93–0.98], P = .06). The diagnostic performance of DE-CTCA was significantly lower in segments with higher coronary artery calcium scoring compared to segments with none or mild calcification, independent of the energy level applied. Conclusions In patients with intermediate to high likelihood of CAD, DE-CTCA had a good diagnostic performance, although significantly lower in segments with severe calcification.